Application of Gost Algorithm For The Safety of Data Sending of General Election - Novan Wijaya (Elkawnie, 2020)
Abstract : The rapid development of the internet has an impact on the security of data sent using internet media. One government agency that uses the internet as data transmission includes the KPU. Data transmission becomes very risky especially the data sent is very important and even confidential. In the internet world, there are many threats and ways to change or retrieve data sent via the internet. Indonesia in particular has conducted direct elections but the data that are in the regions which are the results of recapitulation of the elections will be sent via the internet with a system provided by the KPU. Data from the recapitulation of regional elections becomes very important because it can be changed by intruders. Secure the data sent, methods such as cryptographic techniques that can minimize interference from intruders are needed. One algorithm that can be applied as data security is the GOST algorithm. The GOST algorithm is designed to take a balance between data efficiency and security. Cryptographic techniques that use the GOST algorithm are expected to be able to increase the security of sending election results from various threats without reducing the performance of sending data. The rapid development of the internet has the impact of the security of data sent using internet media. One government agency that uses the internet as data transmission includes the KPU. Data transmission becomes very risky especially the data sent is very important and even confidential. In the internet world, there are many threats and ways to change or retrieve data sent through internet media. Indonesia in particular has conducted direct elections but the data that are in the regions which are the results of recapitulation of the elections will be sent via the internet with a system provided by the KPU. Data from the recapitulation of regional elections becomes very important because it can be changed by intruders. Secure the data sent, methods such as cryptographic techniques that can minimize interference from intruders are needed. One algorithm that can be applied as data security is the GOST algorithm. The GOST algorithm is designed to take a balance between data efficiency and security. Cryptographic techniques that use GOST algorithm can improve the security of sending election results from various threats without reducing the performance of sending data. Election result data that was conducted during the testing was the Ogan Ilir regional election recap data. Tests that have been carried out using the GOST algorithm using WireShark produce stream files sent over the network are not easily identified because they are converted into random strings, so it takes a long time to analyze them.Abstrak : Perkembangan internet yang sangat cepat mempunyai dampak diantranya keamanan data yang dikirim menggunakan media internet. Salah satu instansi pemerintahan yang menggunakan internet sebagai pengiriman data diantaranya KPU. Pengiriman data menjadi sangat beresiko terlebih data yang dikirimkan sangat penting bahkan bersifat rahasia. Didunia internet terdapat banyak ancaman serta cara dalam mengubah atau mengambil data yang dikirimkan melalui media internet. Indonesia pada khususnya telah melakukan pemilu secara langsung tetapi data-data yang berada pada daerah yang merupakan hasil rekapitulasi dari pemilu akan dikirimkan melalui internet dengan sistem yang telah disediakan oleh KPU. Data hasil rekapitulasi pemilu suatu daerah menjadi sangat penting dikarenakan bisa diubah oleh intruder. Untuk mengamankan data yang dikirimkan diperlukan metode seperti teknik kriptografi yang bisa meminimalisir gangguan dari para intruder. Salah satu algoritma yang bisa diterapkan sebagai keamanan data yaitu algoritma GOST. Algoritma GOST dirancang agar mengambil keseimbangan antara efisiensi dan keamanan data. Teknik kriptografi yang menggunakan algoritma GOST mampu meningkatkan keamanan pengiriman data hasil pemilu dari berbagai ancaman tanpa mengurangi performansi dari pengiriman data. Data hasil pemilu yang dilakukan saat pengujian ialah data rekap pilkada Ogan Ilir. Pengujian yang telah dilakukan menggunakan algoritma GOST menggunakan wireshark menghasilkan stream file yang dikirim melalui jaringan tidak mudah diidentifikasi dikarenakan diubah menjadi string acak sehingga membutuhkan waktu yang lama untuk menganalisanya.